#ShoutYourAbortion on Instagram: Exploring the Visual Representation of Hashtag Movement and the Public's Responses. (April 2022) - Kim, Yunhwan; Lee, Sunmi
The goal of the current study was to explore the visual representation of #ShoutYourAbortion hashtag movement on Instagram. The photos' content and embedded texts in the photos were examined. And the photos were clustered using k -means clustering algorithm, and the resulting clustered were compared using the same criteria above. Photo features which shows the content- and pixel-level characteristics were extracted and used for comparison between clusters. The photo features were also used to examine their relationships with the public's responses. It was found that text was the main type of content, and the texts presented in photos were mainly about stories told in first person point of view as a woman. The photos were grouped into two clusters, which differed in terms of content and photo features. And the public's responses were found to be related to photo features. The results are expected to contribute to the understanding of hashtag movements via photos and making photos in hashtag movements more appealing to the public.